THE INTERACTION OF HUMANS AND THE INFORMATION SPHERE IN THE DIGITAL AGE - Kalganov, Mykhailo (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2023)
The article presents the results of the research devoted to the study of the peculiarities of human interaction with the information sphere in the digital age. In particular, the impact of information technologies on human thinking and behavior, social communications and relationships is studied. Special attention is paid to digital platforms and social networks that change human reality, transforming the material context into virtuality. The positive and negative sides of using social networks are also considered, as well as the possible consequences of their use in the long term. In the process of research, the role of information technologies in the modern world and their influence on human behavior and thinking is revealed, the specifics of human interaction with information in the era of information technologies are analyzed, the social and psychological consequences of the use of information technologies and social networks for people are identified, recommendations are developed for the correct use of information technologies and social networks in order to ensure a balanced and healthy human life. It is argued that modern IT has enabled unprecedented access to information and brought people together in new ways, but at the same time created significant challenges such as information overload and the spread of misinformation. It is proven that the development of artificial intelligence and automation of processes is one of the latest trends in the evolution of human interaction with the information sphere, which may eventually lead to radical changes in production processes and the situation on the labor market. The issue of responsible and ethical handling of information technologies is raised due to the significance of their impact on cultural processes on a global scale. The author's argumentation is strengthened by the ideas and opinions of leading modern thinkers on this topic.